Effects of medium composition on Xa den (Ehretia asperula Zoll. et Mor.) cell cultures - Mỹ Trâm, Phạm Thị; Sương, Ngô Kế; Thủy Tiên, Lê Thị (Hue University Journal of Science: Natural Science, 2020)
Xa den (Ehretia asperula Zoll. et Mor.) belongs to the Boraginaceae family and appears in Southeast Asian countries. Xa den is often used to treat diseases such as tumors, emphysema, and detoxification. The effects of plant growth regulators and carbon sources on the formation and proliferation of callus from Xa den leaves in vitro were studied. The results show that callus proliferates well on the medium supplemented with 30 mg/L glucose, 0.4 mg/L 2,4-D, and 0.1 mg/L BA. In this medium, the callus is yellowish-green, friable, and rapid proliferating. After the first subculture, the callus is milky white and friable after 10 weeks of culture. This callus is used as a material for cell suspension cultures. Suspension cells grow in the dark better than in the light with the highest biomass after four weeks of culture (149.933 g/L).